Features of mammalian CNS barrier systems - Johanson, Conrad (Henry Stewart Talks, 2008)
Choroid plexus, Formation of CSF, Permeability of blood, CSF barrier vs. blood-brain barrier, Choroidal secretion of peptides, growth factors and regulatory proteins, Homeostasis and bulk flow of extracellular fluid in the CNS, Impact of CSF dynamics on brain metabolism, Disrupted transport at the blood-CSF interface in hyperthermia, ischemia and Alzheimer's disease, Reduced CSF reabsorption in aging, hydrocephalus and dementia
Archived at 2018/12/10